(untitled) (Baghdad Science Journal, 2025)
Background: Metabolic syndrome MS a cluster of disorders comprising obesity (central and abdominal), dyslipidaemias, glucose intolerance, insulin resistance (or hyperinsulinaemia) and hypertension – is highly predictive of type 2 diabetes mellitus and cardiovascular disease. It should be emphasized that the metabolic syndrome is a syndrome and not a disease. The aim of this study is to evaluate the levels of serum phosphate in different levels in subjects with metabolic syndrome MS and Correlation between serum phosphate levels with metabolic syndrome components. The study was carried out at the National diabetes Center (NDC) /AL-Mustansiryia University ,the period from (Desmber.2011 – May 2012) One hundred forty (140) Iraqi individuals enrolled in the study (100 subject diagnosed as having metabolic syndrome and 40 as control group). The diagnosis of metabolic syndrome was based on Adult Treatment Panel III guidelines. The results of the serum phosphate concentrations in both groups showed that subjects with metabolic syndrome had significantly lower phosphate concentrations 1.52 mg/dl compared with that of control 2.29 mg/dl P?0.0001. The clinical significance of these electrolyte disturbances, as one of the diagnostic criteria of metabolic syndrome. In addition this electrolyte imbalance may have a role in prevention and or treatment of the metabolic syndrome.